Desafíos de la educación colombiana frente a la inclusión de las infancias migrantes venezolanas (2023)
The results of the implementation of a didactic proposal based on ethnomathematics for the strengthening of intercultural dialogue between indigenous peoples and western knowledge are presented. The objective was to evaluate the effectiveness of a didactic strategy for the recognition of the Nasa indigenous people and their own knowledge about weaving with fourth grade students of a school in Bogotá and to establish the relationship between this knowledge and the knowledge proposed in the curriculum for the learning of geometry. For this purpose, an interpretative paradigm and a qualitative methodological approach were used during two phases: the first consisted of interviewing two wise men of the Nasa people to gain access to their own knowledge, and the second consisted of designing and implementing a didactic material during 11 sessions. It was concluded that the development of this type of strategies generates appropriation of cultural and multiethnic diversity and the strengthening of geometric thinking in western students.